2022
DOI: 10.3390/agronomy12061443
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Improves the Salt Tolerance Capacity of Saponaria officinalis by Modulating Its Photosynthetic Rate, Osmoprotectants, Antioxidant Levels, and Ion Homeostasis

Abstract: Salicylic acid (SA) plays an important role in regulating salt stress tolerance in plants. However, there are no studies on the effect of exogenous SA on Saponaria officinalis under salt stress. To study the effectiveness of SA on mitigating salt stress, S. officinalis were used in a pot experiment of salt stress simulated with an NaCl solution (100, 200, and 300 mmol L−1), while an SA solution (0, 0.2, 0.4, 0.6, 0.8, 1.0 mmol L−1) was sprayed on leaves. Under salt stress, spraying SA caused an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Current outcomes revealed that irrigation with saline water considerably decreased the chlorophyll index relative to irrigation with tap water. A decline in chlorophyll has been stated previously in several plants [8,11,12,58]. The deterioration of chlorophyll caused by saline water might be related to boosted chlorophyllase activity [59,60], decreased assimilation of the key chlorophyll pigment complexes encoded by the cab gene family [61], and/or a drop in chlorophyll biosynthesis intermediation concentrations [62].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Current outcomes revealed that irrigation with saline water considerably decreased the chlorophyll index relative to irrigation with tap water. A decline in chlorophyll has been stated previously in several plants [8,11,12,58]. The deterioration of chlorophyll caused by saline water might be related to boosted chlorophyllase activity [59,60], decreased assimilation of the key chlorophyll pigment complexes encoded by the cab gene family [61], and/or a drop in chlorophyll biosynthesis intermediation concentrations [62].…”
Section: Discussionmentioning
confidence: 82%
“…Current results revealed that the spraying of SA boosted chlorophyll accumulation in salt-affected plants. Plants treated with SA had higher levels of chlorophyll than control or salt-affected plants [8,11,58,68,69]. Variations in chlorophyll with SA spraying are advocated to be concentration dependent and species specific [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were previously reported by Gacnik et al [123], who opined that exogenously applied SA accelerated plant growth and development along with enhancing the quality of the traits of Mentha piperita. Xu et al [124] reported that foliar-applied SA in a 0.6 mmol L −1 dose increased the growth of crop plants by preventing electrolyte leakage, and increased the photosynthesis rate in addition to promoting the biosynthesis of chlorophyll, soluble sugar and soluble protein. Additionally, it increased the accumulation of K + , Mg 2+ and Ca 2+ content and the K + /Na + ratio, and maintained ionic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…SA application caused an additional enhancement in photosynthetic rate, osmoprotectants, and antioxidant levels in salinity stress. It also modulates ion homeostasis and ameliorates salinity tolerance in Saponaria officinalis [45].…”
Section: Discussionmentioning
confidence: 99%